The low-cycle fatigue property, damage mechanism and life prediction of compacted graphite iron: Influence of strain rate. (June 2020) - Zou, C.L.; Pang, J.C.; Chen, L.J.; Li, S.X.; Zhang, Z.F.
Graphical abstract: The low cycle fatigue results at different strain rates proved that the dynamic strain aging, oxidation, and grain boundary softening all reduces fatigue life at high temperatures especially combined with the special microstructure of compacted graphite iron. A prediction model for the fatigue life based on quadratic function relation was established and verified. Highlights: The LCF life reduces with the decrease of strain rate at high temperatures. The dynamic strain aging reduces the fatigue life of CGI at 400 °C. Oxidation can induce fatigue crack propagation of CGI at 500 °C. A prediction model for the LCF life was established and verified. Abstract: The low cycle fatigue (LCF) damage mechanism and fatigue life of compacted graphite iron (CGI) at two strain rates were compared and analyzed at different temperatures. The results show that the strain rate has only little effect on the fatigue life of CGI at 25 °C, but the fatigue life reduces significantly with the decrease of strain rate at high temperatures (400 °C, 500 °C). The variation trend of fatigue life at 400 °C may be attributed to the initial cyclic hardening caused by the dynamic strain aging (DSA) effect combined with the serious damage localization of CGI. At 500 °C, the cyclic hardening is inhibited by serious oxidation. The fatigue life decreases with the decrease of strain rate can be ascribed to more oxidative damage and much serious grain boundary cracking. A prediction model for the fatigue life based on quadratic function relation was established through hysteresis energy and the variety of parameters ( W0, β ) was explained by the corresponding damage mechanism. The quadratic relationships between the parameters and temperature can effectively predict the variation tendency of fatigue life versus temperature (0–650 °C).